A Case of Acute Pericarditis After COVID-19 Vaccination - Sonaglioni, Andrea; Albini, Adriana; Noonan, Douglas M.; Brucato, Antonio; Lombardo, Michele; Santalucia, Paola (Frontiers in Allergy, 2021)
A two-dose regimen of Pfizer–BioNTech COVID-19 vaccination confers 95% protection against COronaVIrus Disease 19 (COVID-19) and the safety profile is adequate. To the submission date, there were no reports in literature of acute pericarditis after BNT162b2 vaccination. However, pericarditis has been reported as a rare event associated with COVID-19 infection, which could be due to the pro-inflammatory effects of the spike protein. Recent evidence of post-vaccine myocarditis has been published. Herein we describe the case of a middle-aged healthy women who developed symptoms and signs of acute pericarditis 7–10 days after the second dose of Pfizer–BioNTech COVID-19 vaccination. Although a direct effect cannot be stated, it is important to report a potential adverse vaccine reaction effect that could be associated with the expression of SARS-CoV-2 spike protein induced from the mRNA of the vaccine.